1990
DOI: 10.1084/jem.172.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an exogenous interleukin 6 gene in human Epstein Barr virus B cells confers growth advantage and in vivo tumorigenicity.

Abstract: SummaryThe biological role of interleukin 6 (IL 6) molecules in human B cell tumorigenesis was studied by using an episomal expression vector, pHEBoSV IL6, to introduce stably the human IL6 gene into human Epstein Barr virus (EBV)-transformed B lymphoblasts . The gene was present in the IL6-transfected cells in a high copy number and was efficiently expressed, resulting in the secretion of consistent levels of 11,6 molecules. The constitutive expression of the IL6 gene led to an altered pattern of growth and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 28 publications
2
51
0
Order By: Relevance
“…There is still controversy regarding whether the source of IL-6 in neoplasia is autocrine or paracrine (Kawano et al, 1988;Klein et al, 1989). With respect to B cells infected with EBV, IL-6 has been shown to enhance virus-induced B cell proliferation and Ig production in vitro 30-to 50-fold (Tosato et al, 1988), and to produce human B cell tumours in immunodeficient nude mice in vivo (Scala et al, 1990). The results of our study suggest that IL-6 potentiates EBV-associated lymphogenesis.…”
Section: Discussionsupporting
confidence: 67%
“…There is still controversy regarding whether the source of IL-6 in neoplasia is autocrine or paracrine (Kawano et al, 1988;Klein et al, 1989). With respect to B cells infected with EBV, IL-6 has been shown to enhance virus-induced B cell proliferation and Ig production in vitro 30-to 50-fold (Tosato et al, 1988), and to produce human B cell tumours in immunodeficient nude mice in vivo (Scala et al, 1990). The results of our study suggest that IL-6 potentiates EBV-associated lymphogenesis.…”
Section: Discussionsupporting
confidence: 67%
“…31 While EBV-infected LCL are immortalized but not tumorigenic upon heterotransplantation, the overexpression of IL-6 in LCL cells led to the generation of lymphomas in nude mice. 32 As the effects of PEL cell line-produced IL-6 could be completely inhibited by a neutralizing antibody specific for huIL-6 and as it has been previously shown that vIL-6 was only active in high concentrations (and could not be blocked by the same antibody), 14 we assume that we measured production of huIL-6 in the supernatants of the PEL cell lines. It remains to be seen whether large quantities of vIL-6 are indeed produced physiologically in vivo and whether this is clinically relevant.…”
Section: Figurementioning
confidence: 99%
“…These reports clearly indicate that IL-6 is important for the polyclonal proliferation of B-lineage cells and that the additional genetic changes must be required for the generation of monoclonal neoplasia. As for the transformation of LCLs, the enforced expression of human IL-6 induced colony formation on soft agar and tumorigenicity in nude mice (Scala et al, 1990). Inoculation of peripheral blood lymphocytes from EBV-seropositive donors into the severe combined immunodeficiency (SCID) mice Growth of OS sublines in medium supplemented with 10% (open bar) and 5% (shaded bar) FCS.…”
Section: Figurementioning
confidence: 99%